Antiproliferative activity of aqueous extract of Piper betle L. and Psidium guajava L. on KB and HeLa cell lines - Razak, Fathilah Abdul; Sujata, R.; Norhanom, A.W.; Adenan, M.I. (2010)
The aim of the present study was to assess the effect of the aqueous extracts of Psidium guajava and Piper betle plants on the proliferation of cancerous cell lines, that is, KB and HeLa cell line. Using the neutral red cytotoxicity assay, the IC(50) of P. guajava and P. betle were determined at 29.0 +/- 0.4 and 29.5 +/- 0.3 mu g/ml, respectively, indicating both plant extracts equally potent for the treatment of cancerous oral epidermal lesions. However, a less potent anti-proliferative activity was recorded by P. guajava towards HeLa cell line with an IC(50) of 51.0 +/- 0.6 mu g/ml, whereas P. betle extract did not affect the proliferation of HeLa.